PENGARUH SUBTITUSI PUPUK N SINTETIK DENGAN LIMBAH LUMPUR SAWIT TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS - Johannes Simbolon; Bilman Wilman Simanihuruk; Bambang Gonggo Murcitro; Herry Gusmara; Eko Suprijono (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2018)
[EFFECTS OF PALM OIL SLUDGE SUBTITUTION FOR SYNTHETIC N FERTILIZER ON GROWTH AND YIELD OF SWEET CORN]. Palm oil sludge (POS) contains high concentrations of organic nitrogen dan its can serve as an alternative for synthetic nitrogen fertilizer. Objective of this study was to compare the growth and yield of sweet corn as amended with different compositions of synthetic N fertilizer and palm oil sludge. Six compositions, each containing 138 kg N/ha were assigned as the treatment and arranged in a randomized complete block design with three replications. These were 100% synthetic fertilizer, 80% synthetic fertilizer + 20% POS, 60% synthetic fertilizer + 40% POS, 40% synthetic fertilizer + 60% POS, 20% synthetic fertilizer + 80% POS, and 100% POS. The results of this study indicated that the plot amended with 60% synthetic fertilizer + 40% POS produced the highest plant stature (176.4 cm), stem diameter (2.40 cm), leaf area (8712.82 cm2 ), plant fresh weight (375.19 g), plant dry weight (136.68 g), and husked ear length (17.93 cm). However, the highest observed husked ear yield was only about 61.6 % the yield potential of the sweet corn variety.